2015
DOI: 10.18410/jebmh/2015/784
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Psychiatric Comorbidity in Patients With Alcohol Dependence Syndrome

Abstract: This study was designed to find the prevalence of psychiatric co morbities in patients with alcohol dependence and to assess the risk factors for the same. All the patients with alcohol dependence syndrome (ADS) who presented during the study period were screened. ADS were diagnosed as per ICD-10 criteria. All the patients underwent detailed clinical and neuropsychiatric evaluation. BPRS (Brief Psychiatric Rating Scale) was used to assess psychiatric comorbidities and MINI Scale (Mini International Neuropsychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…(3) Other Indian studies also reported similar observations in their sample. (5,8,12) Females constituted only 2% of the sample in this study similar to another Indian study. (5) A south Indian study concluded that availability of Indian made foreign liquor and living in a village which brewed illicit alcohol were major risk factors for hazardous use in women (13) Both female subjects in our study initiated drinking with their relatives due to false myths about alcohol.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(3) Other Indian studies also reported similar observations in their sample. (5,8,12) Females constituted only 2% of the sample in this study similar to another Indian study. (5) A south Indian study concluded that availability of Indian made foreign liquor and living in a village which brewed illicit alcohol were major risk factors for hazardous use in women (13) Both female subjects in our study initiated drinking with their relatives due to false myths about alcohol.…”
Section: Discussionsupporting
confidence: 87%
“…(7) Such severe alcohol dependence will be associated with high prevalence of psychiatric disorders also. In Kerala, recent prevalence of psychiatric co-morbidity among alcohol dependent inpatients in tertiary care centre was 14% (8) and 66.59% in another deaddiction clinic. (9) DSM-IV reminds clinicians that such mood, anxiety or psychotic symptoms that are documented before severe life problems from alcohol or that remain beyond 4 weeks of total abstinence should be carefully evaluated as possible indicators of true co-morbidity with occurrence of two or more independent psychiatric syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to other recent Indian studies. [7,8,9] DSH was found to be more in males in this study. Most patients with DSH belonged to younger age group with slight male preponderance in other Indian studies.…”
Section: Discussionsupporting
confidence: 55%
“…Most patients with DSH belonged to younger age group with slight male preponderance in other Indian studies. [8,9] But association between gender and deliberate self harm could not be statistically examined because of poor representation of females in this sample. Majority of the sample was less educated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation